2020
DOI: 10.4236/ojog.2020.1030034
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Glycated Hemoglobin in Non-Diabetic Pregnant Women with Preeclampsia: A Case-Control Study in Kinshasa, the Democratic Republic of Congo

Abstract: Background: A disturbed glucose metabolism is quite common during pregnancy. It is due to the diabetogenic potential of pregnancy and responsible for many obstetric complications. The glycated hemoglobin is one of the markers used to depict these disorders. Higher concentrations of this marker would be associated with unfavorable results of pregnancy. Objective: To describe the profile of HbA1c in non-diabetic preeclamptic pregnant women and to establish the association between the values of this marker and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In a study conducted by Mane et al 26 the incidence of macrosomia in the newborns was found to be raised (16.7% from 5.9%) in the participants with HbA1c of ≥5.9% also they found that they had an elevated risk of preeclampsia (9.32% vs. 3.9%). In our present study we did not include variables like macrosomia or preeclampsia but, 17 5.29 Nielsen et al 18 5.0 Yu et al 19 5.0 Bhavadharani et al 20 4.9 Versantvoort et al 21 4.9…”
Section: Discussionmentioning
confidence: 94%
“…In a study conducted by Mane et al 26 the incidence of macrosomia in the newborns was found to be raised (16.7% from 5.9%) in the participants with HbA1c of ≥5.9% also they found that they had an elevated risk of preeclampsia (9.32% vs. 3.9%). In our present study we did not include variables like macrosomia or preeclampsia but, 17 5.29 Nielsen et al 18 5.0 Yu et al 19 5.0 Bhavadharani et al 20 4.9 Versantvoort et al 21 4.9…”
Section: Discussionmentioning
confidence: 94%